Exogenously applied abscisic acid to Yan73 (V. vinifera) grapes enhances phenolic content and antioxidant capacity of its wine. (June 2013) - Xi, Zhu-Mei; Meng, Jiang-Fei; Huo, Shan-Shan; Luan, Li-Ying; Ma, Li-Na; Zhang, Zhen-Wen
<x xml:space="preserve">Abstract</x> Yan73 is a 'teinturier' red wine variety cultivated in China and widely used in winemaking to strengthen red wine colour. The objective of this study was to evaluate the effect of exogenous abscisic acid (ABA) applied to the grapevine cluster on the antioxidant capacity and phenolic content of the wine made from Yan73. Two hundred mg/l ABA was applied on Yan73 grapevine cluster during veraison. As they mature, these ABA-treated and untreated grape berries were transformed into wines, respectively, and the phenolic content and antioxidant capacity of these wines were compared. The results showed that phenolic content (total phenolics, tannins, flavonoids and anthocyanins) and antioxidant capacity were higher in the wine produced with ABA-treated Yan73 grapes than those in the wine from untreated grapes. Compared to Cabernet Sauvignon wine, Yan73 wine had higher phenolic content and stronger antioxidant capacity. These strongly suggest that exogenously applied ABA to Yan73 grapes can enhance phenolic content and antioxidant capacity of its wine, and Yan73 wine has the higher utilization value and potential for development.